Rancang Bangun Penggunaan Venturimeter Fertigasi Pada Irigasi Tetes (Drip Irrigation) - Handayani, Tri; Irawati, Titik; Mustopa, Tarwa; Setyo Utomo, Pamuji (JURNAL ILMIAH AGRINECA, 2025)
Drip irrigation system is one of the solutions to irrigation problems. Drip irrigation applies direct water supply to plant roots. The use of drip irrigation that has been widely used is usually separate from the fertilization or fertigation system. The obstacles that usually occur are blockages in the emitter due to non-homogeneous nutrients and sedimentation. The use of a venturimeter is one solution in fertilization in a drip irrigation system. Fertilizers or nutrients that are distributed in a drip irrigation system have difficulty in determining the right dose due to the mixing of water and fertilizer/nutrients that occurs in the installation pipe. The purpose of this reasearch is to create a design or construction of a venturimeter placement that makes it easier to determine the right fertilizer dose in a drip irrigation system. This research method uses an experimental method with 1 variable, namely the design or design of the venturimeter placement with 2 variables, namely V1: Direct method, V2: Bypass method, with 5 repetitions. The observation variables in this study were the average uniformity of the emitter discharge, the average discharge at the venturimeter input, and the pressure at the venturimeter output. The results obtained were that in the observation of the average uniformity of the CU, the average discharge uniformity reached 98%, while the average output and input venturimeter discharges produced.